Grosor corneal en una muestra de adultos de la población chilena - Romero C., Pablo; Suárez H., Luisa; Aguayo B., Alberto; Huidobro G., Andrés; Sanhueza Z., Felipe (Revista Hospital Clínico Universidad de Chile, 2011)
The central corneal thickness (CCT) is crucial to the estimation of the intraocular pressure (IOP). There are variations among different populations. The objective of the present job was to determine de CCT in a sample of Chilean population. The sample was taken at random from patients attending the office of an ophthalmologist of the Clinical Hospital of the University of Chile. The patients age ranged between 15 and 65 years. We discarded patients with IOP over 21 mm Hg, Spherical Equivalent greater than 6 diopters or with ophthalmological local treatment. The CCT was measured using ulotrasonographyc pachymeter. We enrolled 127 patients and analized 253 eyes. The CCT average was 537,70 μm 39.34 um with an standard deviation of 32.09 um. The CCT of the studied population was less than the reported in Spanish populations in USA, greater Japanese and Afro-Americans and less than Europeans and Chinese. It is important to consider the ethnic variation of the CCT in our population regarding its effect in the correction of the IOP.